Bio-diversified upland rice based cropping systems in Madagascar - CGIAR Research Program on Rice (2021)
The two-year experimentation on diversified rice cropping was concluded: Results showed that sole legume cropping with traditional pulses are the best options in low input cropping systems based on rice upland bi-annual rotations. These recommendations were submitted to the 2nd International Agrobiodiversity Congress, held virtually 15-18 November 2021.